Pola Penggunaan Antibiotik pada Pasien Demam Tifoid di Instalasi Rawat Inap Rsud Waled Tahun 2023 - Bagas Dharma Utama; Sri Marfuati; Rama Samara Brajawikalpa (Universitas Pahlawan Tuanku Tambusai, 2026)
Typhoid fever remains a significant public health problem in developing countries, including Indonesia, with high morbidity rates. Antibiotics are the main therapy for typhoid fever; however, irrational use may lead to antimicrobial resistance, increased treatment costs, and adverse effects. Therefore, evaluating the pattern of antibiotic use is essential to ensure rational therapy and improve patient outcomes. This study aimed to determine the pattern of antibiotic use among typhoid fever patients in the inpatient installation of RSUD Waled in 2023.This study employed a descriptive observational design with a retrospective approach using medical record data. A total sampling technique was applied, resulting in 88 patients who met the inclusion criteria. Variables observed included patient characteristics, types of antibiotics, dosage forms, duration of use, side effects, and allergic responses.The results showed that all patients were confirmed cases (100%), with the majority aged 6–11 years (40.9%) and predominantly male (51.1%). Most patients used BPJS health insurance (96.6%). Cephalosporins were the most frequently prescribed antibiotics (88.6%), mainly administered in parenteral form (77.3%). All patients received antibiotic therapy with appropriate duration according to guidelines (100%), and no side effects or allergic reactions were reported (100%). In conclusion, the pattern of antibiotic use in typhoid fever patients at RSUD Waled in 2023 was consistent with clinical guidelines, dominated by cephalosporin use, and showed no adverse effects or allergic reactions. These findings are important to support rational antibiotic use and to prevent the development of antimicrobial resistance.*